CREATIVITY AND RISK-TAKING PROPENSITY FACTORS IN ENCOURAGING ENTREPRENEURIAL INTENTIONS AMONG HIGH SCHOOL STUDENTS - Hidayah, Shofiyatul; Wibowo, Agus; Mukhtar, Saparuddin; Kundriyah, Kundriyah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The low level of entrepreneurship in Indonesia is caused by a lack of skills among aspiring entrepreneurs. So, concrete steps are needed to improve entrepreneurial skills in the community. One of them is through education, by instilling entrepreneurial intentions since sitting in school. This study was conducted to determine the influence between creativity and risk-taking tendencies on entrepreneurial intentions of SMAN 68 Jakarta students in the Pancasila Student Profile Strengthening Project (P5) entrepreneurship program. The research method used is quantitative research method. The population used in this study were all X-grade students consisting of 275 students with a sample size of 164 students. Research hypothesis testing was carried out using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS) version 4.0.2. The results showed that creativity has a positive and significant influence on entrepreneurial intention, risk-taking tendency has a positive and significant influence on entrepreneurial intention, creativity has a positive and significant influence on risk-taking tendency, and risk-taking tendency has a mediating role in the relationship of creativity to entrepreneurial intention. Researchers provide an understanding of the factors that can increase entrepreneurial intentions, namely creativity and risk-taking tendencies, in P5 entrepreneurship activities in schools.